The Influence of Character Education Based on Local Wisdom on Students' Social and Environmental Behavior - Shakilla Aura; Cacep Supiandi; Derry Nugraha (Social Impact Journal, 2023)
Character education has become the main focus for forming a quality young generation. However, in the context of globalization, integrating local wisdom into character education is important to maintain cultural identity and local values. This research aims to explore the influence of local wisdom-based character education on students' social and environmental behavior. The method used in this research is quantitative, with a questionnaire distributed to secondary school students in an area representing diverse local cultures. The data were analyzed using descriptive and inferential statistical techniques. The research results showed that character education based on local wisdom significantly contributed to improving students' social behavior and environmental awareness. These findings indicate that the integration of local wisdom into character education can be an effective means of strengthening cultural values and increasing environmental awareness. Character education rooted in local wisdom has a significant positive impact on students' social behavior and environmental awareness. Integrating local wisdom into the education curriculum can be an effective strategy for building a young generation that has a strong cultural identity and cares about the environment and a generation that is more responsible and loves the environment.